2010
DOI: 10.1080/02699931003738026
|View full text |Cite
|
Sign up to set email alerts
|

An effect of mood on the perception of geographical slant

Abstract: Previous research has shown that hills appear steeper to those who are fatigued, encumbered, of low physical fitness, elderly, or in declining health (Bhalla & Proffitt, 1999; Proffitt, Bhalla, Gossweiler &Midgett, 1995). The prevailing interpretation of this research is that observers’ perceptions of the environment are influenced by their capacity to navigate that environment. The current studies extend this program by investigating more subtle embodied effects on perception of slant; namely those of mood. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 26 publications
5
80
0
1
Order By: Relevance
“…This complements other findings that individuals with high positive emotions perceive difficult situations to be less challenging as compared to persons who are anxious or depressed [25,26]. Positive affect may also drive other mental health factors (e.g.…”
Section: Predictors Of Successful Agingsupporting
confidence: 38%
“…This complements other findings that individuals with high positive emotions perceive difficult situations to be less challenging as compared to persons who are anxious or depressed [25,26]. Positive affect may also drive other mental health factors (e.g.…”
Section: Predictors Of Successful Agingsupporting
confidence: 38%
“…Furthermore, there is no published evidence to suggest that depression of any severity affects distance perception. In fact, one study shows that depressed individuals do not perceive hills to be steeper than non-depressed individuals (Riener, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that moods affect geographical slant perceptions (Riener, Stefanucci, Proffitt, & Clore, 2011) and pain tolerance (Weisenberg & Tal Raz, 1998). Thus, we included positive and negative moods to Level 1.…”
Section: Hypothesis Testingmentioning
confidence: 99%